Thermal processing of Khoot coal and characterization of obtained solid and liquid products - Batbileg, S; Purevsuren, B; Davaajav, Ya; Namkhainorov, J (Mongolian Journal of Chemistry, 2014)
On 21st January 2015, the abstract of this paper was replaced with the correct abstract. The coal of Khoot deposit have been investigated and determined the technical characteristics, elemental and petrographical maceral compositions. On the basis of proximate, ultimate, petrographic and IR analysis results have been confirmed that the Khoot coal is a sub-bituminous coal. The hard residue after pyrolysis have been activated by heated water steam and determined the iodine and methylene blue adsorption of initial coal and activated carbon samples from pyrolysis hard residue. The porosity structure of initial coal, activated carbon of pyrolysis hard residue and hard residue after thermolysis (thermal dissolution) have been determined by SEM analysis. The liquid tar product of thermolysis of Khoot coal was investigated by FTIR, 13C and 1H NMR spectrometric analysis. The results of thermolysis of Khoot coal in tetralin with constant mass ratio between coal and tetralin (1:1.8) at 450°C show that 60.8% of liquid product can be obtained after thermolysis of the coal organic mass. DOI: http://doi.dx.org/10.5564/mjc.v15i0.326 Mongolian Journal of Chemistry 15 (41), 2014, p66-72